Magnetic field induced finite size effect in type-II superconductors: Spin Models - Schneider, T. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2006)
We explore the occurrence of a magnetic field induced finite size effect on the specific heat andcorrelation lengths of anisotropic type-II superconductors near the zero field transition temperatureTc. Since near the zero field transition thermal fluctuations are expected to dominate and with increasing field strength these fluctuations become one dimensional, whereupon the effect of fluctuations increases, it appears unavoidable to account for thermal fluctuations. Invoking the scaling theory of critical phenomena it is shown that the specific heat data of nearly optimally doped YBa2Cu3O7-d are inconsistent with the traditional mean-field and lowest Landau level predictions of a continuous superconductor to normal state transition along an upper critical fieldHc2(T). On the contrary, we observe agreement with a magnetic field induced finite size effect, whereupon even the correlation length longitudinal to the applied field H cannot grow beyond the limiting magnetic length LHµÖ Ф̅0̅/̅H̅. It arises because with increasing magnetic field the density of vortex lines becomes greater, but this cannot continue indefinitely. LH is then roughly set on the proximity of vortex lines by the overlapping of their cores. Thus, the shift and the rounding of the specific heat peak in an applied field is traced back to a magnetic field induced finite size effect in the correlation length longitudinal to the applied field.